2009
DOI: 10.3151/jact.7.5
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Polycarboxylate Superplasticizers in Ultra-High Strength Concrete: The Importance of PCE Compatibility with Silica Fume

Abstract: Methacrylate ester as well as allylether based polycarboxylates (PCEs) were synthesized to plasticize pastes of cement and silica fume having a water/cement ratio of 0.22. Methacrylate ester copolymers were found to disperse cement well, whereas allylether copolymers are more effective with silica fume. Mechanistic investigations revealed that in cement pore solution, the surface charge of silica fume becomes positive by adsorption of Ca 2+ onto negatively charged silanolate groups present on the silica surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(89 citation statements)
references
References 8 publications
1
69
0
5
Order By: Relevance
“…Therefore, the metal inventory had not been dispersed effectively or incorporated homogeneously into the cement. Whether the presence of ADVA Cast itself is inhibiting metal encapsulation is unclear, although it is noted that bleed water that does not contain superplasticiser is also not The effectiveness of superplasticisers in dispersing colloidal cement phases has been ascribed to early attachment of the polymer to calcium aluminate (C 3 A), which hinders attachment of sulfate ions to form ettringite (Plank et al, 2009). Over time, the superplasticiser is replaced by sulfate (SO 4 2À ) and the cement gains in strength.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the metal inventory had not been dispersed effectively or incorporated homogeneously into the cement. Whether the presence of ADVA Cast itself is inhibiting metal encapsulation is unclear, although it is noted that bleed water that does not contain superplasticiser is also not The effectiveness of superplasticisers in dispersing colloidal cement phases has been ascribed to early attachment of the polymer to calcium aluminate (C 3 A), which hinders attachment of sulfate ions to form ettringite (Plank et al, 2009). Over time, the superplasticiser is replaced by sulfate (SO 4 2À ) and the cement gains in strength.…”
Section: Discussionmentioning
confidence: 99%
“…This shows that in the present case the required amount of SP can be calculated if the composed surface area of all solid ingredients is known. Nevertheless, the SP dosage depends also on the mineralogy and the surface charge of the fines used (Spiratos et al 2003;Plank et al 2009). Another implication of this result is that the SP requirement is rather related to changes in the specific surface area of the mix than to the concentration (by mass) of the nano-silica addition, as it was previously reported by (Sobolev et al 2006).…”
Section: Fresh Concrete Propertiesmentioning
confidence: 99%
“…Park et al (2005) showed that fly ash, finely ground slag and CSF could fill into the voids between cement grains and thus increase the packing density. Plank et al (2009) postulated that the addition of particles finer than cement to fill voids would improve packing and reduce water demand. Sakai et al (2009) revealed that the filling and ball bearing effects of CSF would improve the packing and fluidity of cement paste.…”
Section: Introductionmentioning
confidence: 99%